Pelatihan Pembuatan Kompos Berbantuan Edukit sebagai Solusi Permasalahan Sampah di Desa Kenep, Beji, Pasuruan - Gema Fitriady; Rofiqi, Ainur (Faculty of Cultural Studies, Universitas Brawijaya, 2024)
Kenep Village is a final disposal site which has waste problems and is less than optimal in management. The incoming waste comes from household waste in 11 sub-districts and market waste in Pasuruan Regency with a weight of about 1152 tons/day, while the waste that can be managed reaches 65 tons per day. Therefore, efforts are needed to handle waste from the household level so as not to add to the pile of garbage in the landfill, namely by training in composting which aims to provide education to the community, especially housewives, so that households use kitchen waste to be used as compost. The stages of training include planning, implementation, and reporting. At the planning stage, coordination was carried out with the head of the hamlet, the head of the RT, and the head of the Klaras toga group. In addition, the preparation of tools and materials as well as the manufacture of Edukit was carried out. At the implementation stage, composting training was carried out at the toga park of the Green Eleven Housing. In the implementation stage, compost checks were also carried out every three days and compost multiplication. At the reporting stage, it is done by making activity reports, articles published in the mass media, and service articles. From this training, there was an increase in knowledge and understanding of housewives related to composting based on the questionnaires that had been distributed.